Do Performance–Safety Tradeoffs Cause Hypometric Metabolic Scaling in Animals?. (September 2017) - Harrison, Jon F.
Abstract : Hypometric scaling of aerobic metabolism in animals has been widely attributed to constraints on oxygen (O2 ) supply in larger animals, but recent findings demonstrate that O2 supply balances with need regardless of size. Larger animals also do not exhibit evidence of compensation for O2 supply limitation. Because declining metabolic rates (MRs) are tightly linked to fitness, this provides significant evidence against the hypothesis that constraints on supply drive hypometric scaling. As an alternative, ATP demand might decline in larger animals because of performance–safety tradeoffs. Larger animals, which typically reproduce later, exhibit risk-reducing strategies that lower MR. Conversely, smaller animals are more strongly selected for growth and costly neurolocomotory performance, elevating metabolism. Trends: Animal size does not affect limiting O2 levels, based on physiological tests. Larger animals show no evidence of attempting to compensate for O2 supply limits. Smaller animals have more expensive neuromuscular and anabolic systems. Larger animals have characteristics that reduce risk and energy use. Declining mass-specific ATP demand might cause hypometric scaling of MR.